Kajian Yuridis Tidak Dilaksanakannya Wasiat Oleh Pelaksana Wasiat - Sucianto, Jonathan Reynaldy Budi; Tonata, Ridotaka Sariputra; Budhayati, Christiana Tri (Nagari Law Review, 2024)
A testament is the last will of a person to give his wealth before the person passes away. In implementing a testament, there is often a problem when the testament executor does not execute the testament that the testator has made. This is interesting to analyze because the Civil Code, specifically regarding inheritance law, does not provide clear arrangements regarding the legal consequences of the non-execution of a testament by the executor. This research uses normative legal research, statute approach, and conceptual approach. The results of this analysis state that if the testament executor does not execute the will, then civilly, the testament executor is contrary to his legal obligations as stipulated in Article 1011 jo. Article 1021 of the Civil Code. The testament executor can also be sued based on an illegal act because every action of the testament executor that causes loss to the heirs is considered an unlawful act in accordance with Article 1365 jo. 1367 of the Civil Code.